Correlations Between Cooling Rate, Dendritic Spacing and Hardness in a Brass Alloy for a Variety of Cooling Conditions - Rodrigo André Valenzuela Reyes; Gustavo Paiva Roseiro; Guilherme Lisboa de Gouveia; José Eduardo Spinelli (Materials Research)
As-cast Cu-Zn components can be manufactured under a wide range of solidification conditions, reflected in varying cooling rates. While industrial processes are well-established, the relationships between grain size (GS), dendritic spacing (DS), and cooling rates in Cu-Zn alloys remain barely explored. Such knowledge becomes fundamental since these microstructural features significantly influence mechanical properties such as hardness. Under this context, the present study investigates the solidification behavior of a Cu-30 wt.% Zn alloy through a combination of SEM-EDS, optical microscopy, XRD, and CALPHAD (Calculation of Phase Diagrams) computation. Systematic measurements of average GS and DS have been conducted on samples solidified under unidirectional solidification (US) conditions (slow) and centrifugal casting (CC) in Cu molds (rapid cooling). The ratios between GS and DS have been analyzed and correlated with hardness variations as a function of the solidification rates. Additionally, SEM-EDS and CALPHAD analyses elucidate the formation of phases and Zn segregation patterns under varying cooling conditions. Appropriate approaches to compute cooling rates have been used so that ranges from 0.60 to 0.95 K/s, and from 15 to 47 K/s have been determined for US and CC samples respectively. These findings provide valuable insights into the microstructural evolution and mechanical property optimization of cast brass alloys.